George's Marvellous Medicine - Dahl, Roald (UK, 1981)
George Kranky's grandma is a grouch. She's always mean to George (and not much nicer to his parents either). One day, when George is put in charge of giving Grandma her medicine, he wonders if he can come up with his own remedy to try and help Grandma become less of a grump.
Keywords: Adventure; Juvenile Fiction